Neuroregeneration of injured peripheral nerve by fraction B of catfish epidermal secretions through the reversal of the apoptotic pathway and DNA damage - Al-Arbeed, Taiba A.; Renno, Waleed M.; Al-Hassan, Jassim M. (Frontiers in Pharmacology, 2023)
Crush injuries occur from acute traumatic nerve compression resulting in different degrees of neural damage leading to permanent functional deficits. Recently, we have shown that administration of Fraction B (FB) derived from catfish epidermal secretions accelerates healing of damaged nerve in a sciatic nerve crush injury, as it ameliorates the neurobehavioral deficits and enhances axonal regeneration, as well as protects spinal neurons and increases astrocytic activity and decreasing GAP-43 expression. The present study aimed to investigate the role of FB treatment on the apoptotic pathway in the neuroregeneration of the sciatic nerve crush injury. Male Wistar rats were randomly assigned into five groups: (I) SHAM, (II) CRUSH, (III) CRUSH+(1.5mg/kg)FB, (IV) CRUSH+(3mg/kg)FB, and (V) CRUSH+(4.5mg/kg)FB. Rats underwent sciatic nerve crush surgery, followed by treatment with FB administered intraperitoneally (IP) daily for two weeks and then sacrificed at the end of the fourth week. FB improved the recovery of neurobehavioral functions with a concomitant increase in axonal regeneration and neuroprotective effects on spinal cord neurons following crush injury. Further, FB enhanced Schwann cells (SCs) proliferation with a significant increase in myelin basic protein expression. FB-treated animals demonstrated higher numbers of neurons in the spinal cord, possibly through ameliorating oxidative DNA damage and alleviating the mitochondrial-dependent apoptotic pathway by inhibiting the release of cytochrome c and the activation of caspase-3 in the spinal cord neurons. In conclusion, FB alleviates the neurodegenerative changes in the lumbar spinal cord neurons and recovers the decrease in the neuronal count through its anti-apoptotic and DNA antioxidative properties.